Transcription factor ZNF22 regulates blood-tumor barrier permeability by interacting with HDAC3 protein - Zhu, Baicheng; Zhang, Lu; Zhou, Xinxin; Ning, Hao; Ma, Teng (Frontiers in Molecular Neuroscience, 2022)
Objective The primary goals of this study were to investigate the potential roles of ZNF22 and HDAC3 as a histone deacetylase in regulating an increases in blood-tumor barrier (BTB) permeability and some of the possible molecular mechanisms associated with this effect. Methods The expression of ZNF22 and HDAC3 in glioma-exposed endothelial cells (GECs) of BTB were detected transcription real-time PCR or western blot. The interaction of ZNF22 and HDAC3 in GECs associated with transcript effect was analyzed by means of Co-Immunoprecipitation and luciferase reporter assay. Results In the present investigation, GECs expressed higher levels of ZNF22 as a zinc finger transcription factor and HDAC3 than endothelial cells. We then affirmed that silencing HDAC3 or ZNF22 led to a reduction in BTB permeability. By bioinformatics analysis, chromatin immunoprecipitation (ChIP) assays and luciferase assay, we found that ZNF22 had a target binding relationship with the promoter regions of ZO-1, Occludin, and Claudin-5 and negatively regulated the expression of ZO-1, Occludin, and Claudin-5. Furthermore, we revealed that HDAC3, as a co-transcript repressor with histone deacetylase activity, could interact with ZNF22 to hinder the expression of TJ-associated proteins, thereby further facilitating the permeability of BTB. Conclusion ZNF22 acted as a transcription factor in conjunction with HDAC3 to modulate the expression of TJ-associated proteins, which was correlated with an increase in BTB permeability. These results may provide new strategies and targets for the chemotherapy of gliomas as well as intracranial infections.